Peak exercise capacity prediction from a submaximal exercise test in coronary artery disease patients - Hautala, Arto J.; Kiviniemi, Antti M.; Karjalainen, Jaana J.; Piira, Olli-Pekka; Lepojärvi, Samuli; Mäkikallio, Timo; Huikuri, Heikki V.; Tulppo, Mikko P. (Frontiers in Physiology, 2013)
The purpose of this study was to determine whether a rating of perceived exertion scale (RPE) obtained during submaximal exercise could be used to predict peak exercise capacity (METpeak) in coronary artery disease (CAD) patients. Angiographically documented CAD patients (n = 124, 87% on β blockade) completed a symptom-limited peak exercise test on a bicycle ergometer, reporting RPE values at every second load on a scale of 6 to 20. Regression analysis was used to develop equations for predicting METpeak. We found that submaximal METs at a workload of 60/75 W (for women and men, respectively) and the corresponding RPE (METs/RPE ratio) was the most powerful predictor of METpeak (r = 0.67, p < 0.0001). The final model included the submaximal METs/RPE ratio, body mass index, sex, resting heart rate, smoking history, age, and use of a β blockade (r = 0.86, p < 0.0001, SEE 0.98 METs). These data suggest that RPE at submaximal exercise intensity is related to METpeak in CAD patients. The model based on easily measured variables at rest and during “warm-up” exercise can reasonably predict absolute METpeak in patients with CAD.